Energy balance for ethyl alcohol production from crops - Silva, José Gomes da [UNESP]; Serra, Gil Eduardo [UNESP]; Moreira, José Roberto; Conçalves, José Carlos; Goldemberg, José (Amer Assoc Advancement Science, 1978)
Energy requirements to produce ethyl alcohol from three different crops in Brazil (sugarcane, cassava, and sweet sorghum) were calculated. Figures are presented for the agricultural and industrial phases. The industrial phase is always more energy-intensive, consuming from 60 to 75 percent of the total energy. Sugarcane is the more efficient crop for ethyl alcohol production, followed by sweet sorghum and cassava from a net energy viewpoint. The utilization of sweet sorghum stems might increase the total energy gain from this crop to almost the same level as sugarcane. Cassava has a lower energy gain at the present state of agriculture in Brazil. Copyright © 1978 AAAS.